TINGKAT KEPUASAN KONSUMEN DALAM MENGONSUMSI PRODUK MINUMAN KOPI BERDASARKAN ATRIBUT PRODUK (Studi Kasus KL Coffee Bandar Lampung) - Dian Febrianingsih; Fadila Marga Saty; Irmayani Noer; Fitriani Fitriani (Universitas Galuh, 2023)
The rise of coffee shops in Bandar Lampung causes people to have many choices according to the wishes of the community. One of the coffee shops that has survived the rapid development of the coffee shop business in Bandar Lampung is KL Coffee. This final project aims to describe the characteristics of KL Coffee consumers, analyze the level of satisfaction and recommendations for improvement of KL Coffee priorities, as well as to determine the loyalty of KL Coffee consumers. The sampling technique used in this study is Accidental Sampling. Respondents in this study amounted to 52 respondents. The data analysis methods used are descriptive analysis, Customer Satisfaction Index (CSI) analysis, Importance Performance Analysis (IPA), and Net Promoter Score (NPS). The results showed that the characteristics of KL Coffee respondents were 78.85% of respondents aged 21-25 years, dominated by female consumers as many as 61.54% of respondents, as many as 88.46% of respondents were unmarried, 50% of respondents had a D4/S1 education, with 46.15% of respondents have pocket money/income per month as much as Rp. 500,000 – Rp. 2,500,000, as well as family members 1-4 people as much as 50% of respondents and 5-8 people as much as 50% of respondents. The results of the analysis using the Customer Satisfaction Index (CSI) method show that the level of customer satisfaction is 87.80% which is included in the very satisfied category. Recommendations for improvement for KL Coffee are instruments that are in quadrant I of the Cartesian diagram of Importance Performance Analysis (IPA) there are 4 instruments, namely consumers hope that the price of products offered by KL Coffee is affordable with quality, consumers hope that the products served have a stable taste in every season. the presentation. The results of the calculation of the Net Promoter Score (NPS) obtained a result of 30.77% which is included in the loyal category.